2018
DOI: 10.3389/fphar.2018.00801
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacology of Berberine Based on Multi-Target Binding Motifs

Abstract: Background: Polypharmacology is emerging as the next paradigm in drug discovery. However, considerable challenges still exist for polypharmacology modeling. In this study, we developed a rational design to identify highly potential targets (HPTs) for polypharmacological drugs, such as berberine.Methods and Results: All the proven co-crystal structures locate berberine in the active cavities of a redundancy of aromatic, aliphatic, and acidic residues. The side chains from residues provide hydrophobic and electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…The higher affinity exhibited by CO compared to CH and SA can be due to the faster association phase. Our data are in agreement with a previous study [ 80 ] that showed the ability of berberine-like inhibitors of Aβ 1-42 to interact with the polypeptide at low micromolar K D values [ 80 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The higher affinity exhibited by CO compared to CH and SA can be due to the faster association phase. Our data are in agreement with a previous study [ 80 ] that showed the ability of berberine-like inhibitors of Aβ 1-42 to interact with the polypeptide at low micromolar K D values [ 80 ].
Fig.
…”
Section: Resultssupporting
confidence: 93%
“…4 ) suggested the formation of complexes, in a concentration-dependent manner. Freshly dissolved Aβ 1-42, after HFIP treatment, was covalently immobilized on Sensor chip [ 80 ]. Kinetic parameters, reported in Table 1 , allowed the estimation of thermodynamic dissociation constant values that appear in the low, for CO, high, for SA, and very high, for CH, micromolar range.…”
Section: Resultsmentioning
confidence: 99%
“…Among the numerous classes of compounds, mostly related to traditional DNA binders, that have been successfully developed as G4-DNA ligands [17], the natural product berberine (1a) has attracted special attention. Berberine (1a) is an isoquinoline alkaloid with an exceptionally wide range of biological activities [23,24]. It has been shown that berberine (1a) and its derivatives act, for example, as anti-inflammatory [25], antibacterial [26,27], and anticancer reagents [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, the BACE1 inhibitory activity of berberine (11) was found to be less (IC 50 value > 100 µM) [67]. In another study, through surface plasmon resonance (SPR) binding analysis and docking studies, the direct binding of berberine and BACE-1 was illustrated [68]. Reports of berberine acting on the BACE1 expression levels are also available, hence, further studies are required for the identification of the potential mechanism of action of the compound [69].…”
Section: Alkaloids Showing Inhibition Of Beta-site Amyloid Precursor mentioning
confidence: 99%